Interannual Variability of Rainfall over Indonesia: Impacts of ENSO and IOD and Their Predictability. Issue 1 (January 2016) - Hidayat, R; Ando, K; Masumoto, Y; Luo, J J
Abstract: Northwestern Java and Makassar rainfall variations are examined in relation to the tropical air-sea coupled phenomena referred to as the Indian Ocean Dipole (IOD) and El Nino- Southern Oscillation (ENSO) using retrospective forecasts known as SINTEX-F. The model predicts the rainfall and its variability realistically in September-November (SON) and in general successfully predicts the interannual variation of northwestern Java rainfall up to 3 months ahead and Makassar rainfall up to 6 months ahead. This indicates potential societal benefits of rainfall predictability in Indonesia. Simple correlation analysis based on observations and model predictions reveals significant influence of IOD and ENSO on the northwestern Java and Makassar. However, the correlation between ENSO and the northwestern Java rainfall becomes insignificant if the IOD influence is excluded. Similarly, the correlation between IOD and Makassar rainfall becomes insignificant if excluding the ENSO influence. These results confirm that a major portion of interannual variation of the northwestern Java (Makassar) rainfall is related to IOD (ENSO) event.